Analisis Perbandingan Pembiayaan Kredit Usaha Rakyat (KUR) Dalam Bank Konvesional dan Bank Syariah Terhadap UMKM (Studi Kasus UMKM Medan) - Ariesa, Yeni; Ginting, Emya Pebina Br; Silitonga, Aldi Neri (CV. ITTC INDONESIA, 2024)
People's Business Credit (KUR) for MSMEs is distributed through two banking systems: conventional and sharia. The basic comparison between the two is in their operational principles. Conventional banks have an interest system, while Islamic banks have a profit sharing principle. This study is targeted at comparing People's Business Credit (KUR) financing at conventional banks and sharia banks for Medan city MSMEs. This study takes a quantitative approach. This study uses primary data obtained by conducting direct interviews at the KUR section of BTN bank KCP Setiabudi and the KUR section of BSI bank KC Gajah Mada. The results of the study are (1) there is an impact of BTN bank and BSI bank KUR financing on MSMEs (2) there is a significant comparison between conventional bank KUR financing and sharia bank financing (3) there is a significant comparison between conventional bank MSMEs and sharia bank MSMEs.